Opacities for photon splitting and pair creation in neutron star magnetospheres. Issue 3 (10th April 2019) - Hu, Kun; Baring, Matthew G; Wadiasingh, Zorawar; Harding, Alice K
ABSTRACT: Over the last four decades, persistent and flaring emission of magnetars observed by various telescopes has provided us with a suite of light curves and spectra in soft and hard X-rays, with no emission yet detected above around 1 MeV. Attenuation of such high-energy photons by magnetic pair creation and photon splitting is expected to be active in the magnetospheres of magnetars, possibly accounting for the paucity of gamma-rays in their signals. This paper explores polarization-dependent opacities for these two QED processes in static vacuum dipole magnetospheres of highly magnetized neutron stars, calculating attenuation lengths and determining escape energies, which are the maximum photon energies for transparency out to infinity. The numerical trajectory integral analysis in flat and curved space–times provides upper bounds of a few MeV or less to the visible energies for magnetars for locales proximate to the stellar surface. Photon splitting opacity alone puts constraints on the possible emission locales in their magnetospheres: regions within field loops of maximum altitudes r_max2\!-\!4 stellar radii are not commensurate with maximum detected energies of around 250 keV. These constraints apply not only to magnetar flares but also to their quiescent hard X-ray tail emission. An exploration of photon splitting attenuation in the context of a resonant inverse Compton scattering model for the hard X-ray tails derives distinctive phase-resolved spectroscopic and polarimetric signatures, of significant interest for future MeV-band missions such as AMEGO and e-ASTROGAM.